Uneven Participation: Socio‐Territorial Inequality and Political Participation in Buenos Aires. - Annunziata, Rocío; Halvorsen, Sam; Mauro, Sebastián (Bulletin of Latin American Research, 2026)
How do socio‐territorial inequalities – i.e. social inequalities embedded in urban space – relate to political participation? Based on qualitative fieldwork conducted in the poorest and richest neighbourhoods of Buenos Aires, we identified contrasting patterns regarding three aspects: motivations of participation, repertoires and state response. We conclude that participatory patterns in strongly unequal cities tend to reproduce rather than attenuate the uneven exercise of citizenship.